Positive Solutions for a Class of Singular Boundary Value Problems with Fractional q-Difference Equations. (6th April 2015) - Wang, Jufang; Yu, Changlong; Guo, Yanping
Abstract : We discuss a class of singular boundary value problems of fractionalq -difference equations. Some existence and uniqueness results are obtained by a fixed point theorem in partially ordered sets. Finally, we give an example to illustrate the results.